PENDEKATAN DISCOURSE ANALYSIS UNTUK MEMAHAMI KONTEKS SOSIAL DAN IDEOLOGIS DALAM PENDIDIKAN - Safitri, Nopira; Sri Murhayati (Al-Ihda' : Jurnal Pendidikan dan Pemikiran, 2023)
This research examines the Discourse Analysis method as a qualitative approach in understanding the meaning of texts or conversations in social, cultural, and ideological contexts. Through literature study, discourse analysis is used to explore the hidden meaning behind complex social phenomena, by highlighting the role of language as a means of communication. It includes various approaches, such as narrative, Marxist, psychoanalytic and framing discourse analysis, to understand how meaning, ideology and power are shaped and transmitted. The results show that discourse analysis helps identify ideologies, rhetoric and social contexts that influence the production and reception of texts. In addition, the method provides great insight into the relationship between language, power and social interaction, making it relevant to a wide range of disciplines, including communication, sociology and cultural studies. Keywords: Discourse Analysis, Qualitative Method